Notations of the wild : ecology in the poetry of Wallace Stevens - Voros, Gyorgyi, 1953- (University of Iowa Press, 1997)
In the summer of 1903, just before he turned twenty-four, Wallace Stevens joined a six-week hunting expedition to the wilderness of British Columbia. The adventure profoundly influenced his conceptions of language and silence, his symbolic geography, and his sensibilities toward wild nature as nonhuman "other." The rugged western mountains came to represent that promontory of experience-"green's green apogee"--Against which Stevens would measure the reality of all his later perceptions and conceptions and by which he would judge the purpose and value of works of the human imagination. Notations.